Smart Cities in Canada: Digital Dreams, Corporate Designs - Valverde, Mariana; Flynn, Alexandra (Allard Research Commons, 2020)
Experts from across the country investigate the "smart city" trend in urban planning as it is showing up in different Canadian municipalities. "Smart cities" use surveillance, big data processing and interactive technologies to reshape urban life. Transit riders can see the bus coming on a map on their phones. Cities can measure and analyze the garbage collected from every household. Businesses can track individuals' movements and precisely target advertisements. Google's failed Sidewalk Labs proposal in Toronto, which drew sharp criticism over surveillance and privacy concerns, is just one of the many smart city projects which have been proposed or are underway in Canada. Iqaluit, Edmonton, Guelph, Montreal, Toronto and other cities and towns are all grappling with how to use these technologies. Some cities have quickly partnered with digital giants like Uber, Bell and IBM. Others have kept their distance. Big tech companies are hard at work recruiting customers and shaping – sometimes making – public policy on data collection and privacy. Smart Cities for Canada: Promise and Perils is the first book on smart cities in Canada. In this collection, experts from across the country investigate what this new approach means for the problems cities face, and expose the larger issues about urban planning and democracy raised by smart city technology. This is a valuable, timely, independent‐minded book for Canadians. [From Smart Cities in Canada: Digital Dreams, Corporate Designs - Lorimer Adult ] https://commons.allard.ubc.ca/books/1092/thumbnail.jpg